Is it safe to use intravenous iron sucrose during pregnancy? A randomized controlled trial - Dubey, Sunita; Suri, Vanita; Aggarawal, Neelam; Das, Reena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: To compare the efficacy and safety of intravenous iron sucrose to oral iron in the treatment of iron deficiency anemia in pregnancy. Methods: In this randomized trial 200 pregnant women with hemoglobin between 7g/dl and 9g/dl and serum ferritin <15 ng/ml received either iron sucrose or oral iron sulphate. The iron sucrose dose was calculated from the following formula: weight (kg) x (110 g/l – actual hemoglobin (g/l) x 0.24 + 500mg. Treatment efficacy was assessed by clinical and laboratory response on 2nd week, 4th week of therapy, after that 4th weekly till delivery.Statistical analysis was done with paired and independent samples “t” test applied. Hemoglobin measurements were analyzed by repeated- measures of analysis of variance with Huynh and Feldt corrections. Serum ferritin measurement across the time within each group was analyzed by two sample test with equal variance .Adverse drug reactions, fetal weight, blood transfusions were also recorded. Results: The significant rise in hemoglobin from 8.0 ± 0.79gm/dl to10.80± 0.61gm/dl in intravenous group as compared to oral iron group from 8.19 ± 0.60gm/dl to 9.86± 0.61 gm/dl was seen at 4th week of treatment (P = 0.000).After 2 week of treatment rise in serum ferritin values were higher in intravenous group from 6.25± 1.05 ng/ml; to 155.33± 57.4 ng/ml and in oral group from5.71± 1.71ng/ml to20.8 ±9.5 ng/ml ( p=.000 ).No serious adverse drug reactions were observed in intravenousgroup. Conclusion: Iron sucrose is safe to use during pregnancy. It raises hemoglobin and restores iron stores faster than oral iron.